Retrospective Analysis of RSV Infection in Pediatric Patients: Epidemiology, Comorbidities, Treatment, and Costs in Dubai (2014-2023) - Jean Joury; Nawal Al Kaabi; Sara Al Dallal; Bassam Mahboub; Mostafa Zayed; Mohamed Abdelaziz; Jennifer Onwumeh-Okwundu; Mark A. Fletcher; Subramanyam Kumaresan; Badarinath C. Ramachandrachar; Mohamed Farghaly (Journal of Health Economics and Outcomes Research)
**Background:** Infections attributable to respiratory syncytial virus (RSV) are a major cause of hospitalization among young children worldwide. Despite substantial clinical and economic burden, real-world data associated with RSV infections in the United Arab Emirates (UAE) are limited. **Objectives:** This study aimed to assess among children (<18 years) diagnosed with RSV the epidemiology, seasonality, comorbidities, treatment patterns, length of hospital stay, healthcare resource utilization (HCRU), and costs associated with pediatric infection in Dubai, UAE. **Methods:** This 10-year retrospective cohort study (Jan. 1, 2014–Sept. 30, 2023) utilized Dubai Real-World Database, a private insurance claims database. Patients aged <18 years with a first-episode diagnosis claim (primary or secondary, or a hospital admission) for RSV any time during the index period (Jan. 1, 2014–June 30, 2023) were included. Outcomes were analyzed during a 3-month follow-up. Patients were stratified into 3 cohorts: Cohort 1 (<2 years), Cohort 2 (2 to <6 years), and Cohort 3 (6 to <18 years). **Results:** Of 28 011 patients identified, 25 729 were aged <18 years with RSV infection. An increasing trend in reported cases was observed from 2014 to 2022, with an average annual increase of 55%. Half of study patients (49.3%) belonged to Cohort 1, with a mean age of 0.6 years, while less than 2% had known risk factors and 22% of the patients in cohort 1 were hospitalized. In Cohort 1, 32.0% had upper respiratory tract infections, 39.4% had lower respiratory tract infections, and 44.4% of patients had an “other respiratory disease.” The average length of hospitalization was about 4 days across all cohorts. The total hospitalization cost was highest in patients <2 years, amounting to US $9 798 174 (median, US $2241.30). **Conclusion:** Among the RSV patients, 49.3% were <2 years of age and few had recognized risk factors. Among patients <2 years, 22% were hospitalized, with an average hospital stay of 4 days; the cost of hospitalization totaled US $9 798 174. These findings can inform healthcare stakeholders about future policy measures and the need for effective preventive strategies.